Redefining Management Accounting Systems : A Systematic Review of Recent Advances and Future Directions - Ramadanty, Jesica; Putri, Mareta (Indonesian Journal Publisher, 2024)
Management accounting systems (MAS) have evolved significantly over the past decades in response to dynamic business environments, technological innovations, and the increasing complexity of organizational structures. This article systematically reviews recent developments in MAS, identifying key trends, methodologies, and applications. Through an in-depth analysis of contemporary literature, we explore the transformation of traditional MAS and propose future directions for research and practice. The review focuses on integrating advanced analytics, the role of sustainability in decision-making, and the increasing importance of digital transformation in redefining MAS. Our findings suggest a paradigm shift towards more flexible, data-driven systems capable of supporting strategic decision-making in real time.